Astronaut out-of-vehicle cable

By using graphene oxide/carbon nanocomposite fibers and 3D-MXene@M electromagnetic shielding layer in astronaut outlet cables, the interference problem of electromagnetic radiation on signal transmission in space environment is solved, and more efficient electromagnetic shielding and signal stability are achieved.

CN119340016BActive Publication Date: 2025-03-18HUNANVALIN WIRE&CABLE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411870695.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-18
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

Electromagnetic radiation in space environments interferes with cable signal transmission of traditional metal materials, affecting the quality of communication and data transmission between astronauts and spacecraft or ground control centers.

Method used

The composite fiber precursor is prepared by electrospinning technology by using an electromagnetic shielding layer including matrix resin, graphene oxide/carbon nanocomposite fibers and 3D-MXene@M, and pre-oxidation and carbonization are carried out under air and nitrogen protection to form a porous structure to enhance electromagnetic shielding performance.

Benefits of technology

Effectively reduce the self-weight of the cable, increase the payload of the launching rocket, and significantly enhance the electromagnetic shielding performance in outer space to ensure the stability and quality of signal transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340016B_ABST
    Figure CN119340016B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of cable technology, and specifically to an astronaut extravehicular cable, comprising an outer sheath and a mica wrapping tape layer and an electromagnetic shielding layer arranged on the inner side of the outer sheath, wherein the electromagnetic shielding layer covers and fixes a plurality of cable cores, and the cable cores are composed of a conductor and an inner sheath; the electromagnetic shielding layer comprises a matrix resin, graphene oxide / carbon nanocomposite fibers and 3D‑MXene@M, wherein M is a transition metal element. The electromagnetic shielding layer in the present invention has good mechanical properties and excellent electromagnetic shielding effectiveness. The astronaut extravehicular cable prepared by the electromagnetic shielding layer can effectively resist electromagnetic radiation from outer space, maintain stable transmission of signals in the cable, and has broad application prospects in outer space exploration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cables, in particular to an astronaut extravehicular cable. Background Art

[0002] Astronaut extravehicular cables, also known as umbilical cables, play a vital role in outer space exploration. As an important lifeline for astronauts during spacewalks, they need to provide astronauts with various vital signs data (such as heart rate, blood pressure, body temperature, etc.) during extravehicular activities and the scientific research data they collect, and transmit them back to the spacecraft or space station in real time and accurately. These data are crucial for monitoring the physical condition of astronauts and ensuring their safety. In addition, they also undertake the communication tasks between astronauts and spacecraft or ground control centers, ensuring that astronauts can keep in touch with the team at any time during extravehicular activities, receive instructions and report situations.

[0003] However, the space environment is extremely harsh, especially the electromagnetic radiation in outer space can cause electromagnetic interference to signal transmission in cables. This interference may cause signal distortion, attenuation or interruption, affecting the quality of communication and data transmission between astronauts and spacecraft or ground control centers, and having an adverse impact on astronauts' safety. Traditional metal materials have good electrical conductivity and have been used in the field of electromagnetic shielding relatively early, but their high density has also limited their application in outer space exploration to a certain extent. Summary of the invention

[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes an astronaut extravehicular cable.

[0005] The technical solutions adopted are as follows:

[0006] An astronaut out-of-vehicle cable comprises an outer sheath, and a mica wrapping tape layer and an electromagnetic shielding layer arranged inside the outer sheath, wherein the electromagnetic shielding layer covers and fixes a plurality of cable cores, and the cable cores are composed of a conductor and an inner sheath;

[0007] The electromagnetic shielding layer comprises a matrix resin, graphene oxide / carbon nanocomposite fibers and 3D-MXene@M, wherein M is a transition metal element.

[0008] Furthermore, the preparation method of the electromagnetic shielding layer is as follows:

[0009] Polyacrylonitrile and a porogen are dissolved in an organic solvent, and graphene is added to prepare an electrospinning solution, a composite fiber precursor is prepared by an electrospinning machine, the composite fiber precursor is dried and the porogen is removed to form a porous structure, a pre-oxidation treatment is performed in an air atmosphere, and then a carbonization treatment is performed under nitrogen protection to obtain a graphene oxide / carbon nanocomposite fiber with a porous structure;

[0010] Disperse MXene in a quaternary ammonium salt solution at 40-60°C and stir for 12-36 hours before filtering. The resulting solid is frozen with liquid nitrogen and then freeze-dried in a freeze dryer to obtain 3D-MXene. Form an M layer on its surface by chemical plating to obtain 3D-MXene@M.

[0011] The matrix resin, 3D-MXene@M and graphene oxide / carbon nanocomposite fibers are prepared into a slurry, and then a film is formed by a casting method.

[0012] Furthermore, the preparation method of the electromagnetic shielding layer is as follows:

[0013] Appropriate heating is performed to dissolve polyacrylonitrile and porogen PVP in DMF to obtain a polyacrylonitrile solution, and then graphene is added for ultrasonic oscillation to prepare an electrospinning solution, and an appropriate amount of the electrospinning solution is injected into a syringe, and the distance between the needle and the receiver is 10-20 cm, the voltage is set to 10-30 kV, and the spinning speed is 0.1-1 ml / h. Electrospinning is performed, and the collected nanofibers are vacuum dried to obtain a composite fiber precursor, and the composite fiber precursor is soaked and washed in deionized water at 100° C. to remove the porogen PVP to form a porous structure, and then placed in a muffle furnace for pre-oxidation treatment in an air atmosphere, and then carbonized under nitrogen protection to obtain a graphene oxide / carbon nanocomposite fiber with a porous structure;

[0014] Take commercially available MXene (Ti3C2T x ) is dispersed in an octadecyltrimethylammonium bromide solution, stirred for reaction under water bath heating conditions, and then filtered. The obtained solid is washed with deionized water and then frozen with liquid nitrogen to form, and then placed in a freeze dryer for freeze drying to obtain 3D-MXene. The 3D-MXene is added to a SnCl2 solution for sensitization treatment, and then added to a PdCl2 solution for activation treatment. Finally, the product is washed with deionized water until neutral and added to a chemical plating solution for copper plating to obtain 3D-MXene@Cu. The composition of the chemical plating solution is as follows: 10-20g copper sulfate, 20-30g potassium sodium tartrate, 0.01-0.1g thiourea, 5-10g formaldehyde, 4-8g sodium hydroxide, 0.1-0.5g ammonium chloride, 0.1-0.5g sodium silicate, and water is added to 1000ml;

[0015] PVA resin, PTFE resin, graphene oxide / carbon nanocomposite fiber, 3D-MXene@Cu and casting components (anhydrous ethanol, xylene, polyvinyl butyral, oleic acid, glycerol, dibutyl phthalate in a mass ratio of 8:8:2:1:0.5:0.5) are mixed, and the mixture is ball-milled on a planetary ball mill to obtain a slurry. The slurry is vacuum-defoamed and then cast on a flat glass plate to form a film. The obtained film is kept warm in an oven and cooled to room temperature along with the furnace.

[0016] Furthermore, 3D-MXene has a three-dimensional flower-like layered structure;

[0017] Furthermore, the porogen is any one or more combinations of polyethylene glycol, hydroxypropyl cellulose, povidone, urea, and polyvinyl pyrrolidone, preferably polyvinyl pyrrolidone PVP.

[0018] Furthermore, the mass ratio of polyacrylonitrile to porogen PVP is 1-5:1-5.

[0019] Furthermore, the pre-oxidation temperature is 200-400°C, and the carbonization temperature is 800-1000°C.

[0020] Furthermore, the quaternary ammonium salt is alkyl trimethyl ammonium bromide, wherein the number of carbon atoms of the alkyl group is ≥10, and is preferably octadecyl trimethyl ammonium bromide.

[0021] Furthermore, 3D-MXene aerogel needs to be sensitized and activated before chemical plating.

[0022] Furthermore, the organic solvent is a dipolar solvent, and the dipolar solvent is selected from dimethyl sulfoxide DMSO, dimethylformamide DMF, acetone, acetonitrile, dimethylacetamide DMAC, and hexamethylphosphoramide HMP.

[0023] Furthermore, the mass ratio of the matrix resin, graphene oxide / carbon nanocomposite fibers and 3D-MXene@M is 10-50:1-5:1-5.

[0024] Furthermore, the matrix resin is any one or more combinations of polyvinyl alcohol resin, epoxy resin, polyester resin, bismaleimide resin, thermosetting polyimide resin, furan resin, polybutadiene resin, silicone resin, polytetrafluoroethylene resin, and polyvinylidene fluoride resin, preferably polyvinyl alcohol resin and polytetrafluoroethylene resin, and the mass ratio of the polyvinyl alcohol resin to the polytetrafluoroethylene resin is 1-10:1-10.

[0025] Furthermore, M is any one of Ni, Ag, and Cu, preferably Cu.

[0026] Beneficial effects of the present invention:

[0027] The present invention provides an astronaut extravehicular cable, which uses an electromagnetic shielding layer to replace the current conventional metal-based electromagnetic shielding material, which can effectively reduce the cable's own weight and increase the payload of the launch rocket. Carbon materials have become one of the most popular materials in electromagnetic shielding due to their outstanding electrical conductivity, excellent flexibility, environmental friendliness, easy manufacturing and stable chemical properties. The graphene oxide / carbon nanocomposite fiber in the present invention can form a conductive network in the electromagnetic shielding layer, and achieve electromagnetic shielding of electromagnetic radiation by absorption, reflection and scattering. Its unique porous structure can increase the number of reflections of electromagnetic waves and the absorption loss of electromagnetic waves, thereby achieving enhanced electromagnetic shielding performance;

[0028] The excellent electrical conductivity of MXene makes it have broad application value in the field of electromagnetic shielding. In the present invention, quaternary ammonium salt intercalation and liquid nitrogen cryogenic freezing technology are used to increase the interlayer spacing of MXene. Under the action of hydrogen bonds between MXene layers and between MXene layers and water molecules, they self-assemble into a stable three-dimensional flower-like layered structure. Compared with the traditional two-dimensional sheet structure, this structure has better electromagnetic shielding performance and also provides active sites for the attachment of transition metal particles. 3D-MXene@M can form a composite three-dimensional conductive network with graphene oxide / carbon nanocomposite fibers. Its unique core-shell structure produces multiple forms of energy dissipation such as dielectric loss, magnetic loss, interface polarization loss and multiple reflection loss, showing an excellent shielding mechanism for electromagnetic radiation, so that the electromagnetic shielding layer in the present invention has good mechanical properties and excellent electromagnetic shielding effectiveness. The astronaut extravehicular cable prepared by the MXene can effectively resist electromagnetic radiation from outer space and maintain stable transmission of signals in the cable, and has broad application prospects in outer space exploration. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a schematic diagram of the structure of the astronaut extravehicular cable provided in Example 1, in which the reference numerals represent:

[0030] 1-X-ETFE outer sheath, 2-mica wrapping tape layer, 3-electromagnetic shielding layer, 4-ETFE inner sheath, 5-silver-plated copper stranded conductor;

[0031] Figure 2 This is the SEM image of the 3D-MXene prepared in Example 1, which shows that it has a three-dimensional flower-like layered structure. DETAILED DESCRIPTION

[0032] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters. Example 1

[0033] A cable for astronauts to leave the spacecraft. Figure 1 The structure is a flat belt, including an X-ETFE outer sheath 1, a mica wrapping tape layer 2 and an electromagnetic shielding layer 3 arranged inside the X-ETFE outer sheath 1, the electromagnetic shielding layer 3 covers and fixes three cable cores, and each cable core is composed of an ETFE inner sheath 4 and a silver-plated copper stranded conductor 5;

[0034] The electromagnetic shielding layer 3 includes PVA resin, PTFE resin, graphene oxide / carbon nanocomposite fiber and 3D-MXene@Cu in a mass ratio of 20:5:1:1;

[0035] The preparation method of the electromagnetic shielding layer 3 is as follows:

[0036] Appropriate heating was performed to dissolve 8 g of polyacrylonitrile and 4 g of porogen PVP in 100 ml of DMF to obtain a composite solution, and then 0.1 g of graphene was added and ultrasonically oscillated for 30 min to prepare an electrospinning solution, and an appropriate amount of the electrospinning solution was injected into a syringe, and the distance between the needle and the receiver was 15 cm, the voltage was set to 20 kV, and the spinning speed was 0.5 ml / h. Electrospinning was performed, and the collected nanofibers were vacuum dried for 12 h to obtain a composite fiber precursor, and the composite fiber precursor was soaked in deionized water at 100 ° C for 2 h to wash and remove the porogen PVP to form a porous structure, and then placed in a muffle furnace and heated to 200 ° C at a rate of 1 ° C / min in an air atmosphere for pre-oxidation treatment for 5 h, and then heated to 800 ° C at a rate of 10 ° C / min under nitrogen protection for carbonization treatment for 2 h to obtain a graphene oxide / carbon nanocomposite fiber with a porous structure;

[0037] Take commercially available MXene (Ti3C2T x ) 5g was dispersed in 10wt% 500ml octadecyltrimethylammonium bromide solution, stirred in a water bath at 40℃ for 24h and filtered. The obtained solid was washed with deionized water and frozen with liquid nitrogen. It was then placed in a freeze dryer and freeze-dried at -80℃ and 10 Pa for 48h to obtain 3D-MXene. Figure 2 This is the SEM image of the prepared 3D-MXene, which shows that it has a three-dimensional flower-like layered structure. The 3D-MXene was added to a 10 g / L SnCl2 solution for sensitization treatment for 30 min, and then added to a 0.1 g / L PdCl2 solution for activation treatment for 30 min. Finally, the product was washed with deionized water until neutral and added to a 40°C chemical plating solution for copper plating for 2 min to obtain 3D-MXene@Cu. The composition of the chemical plating solution is as follows: 10 g copper sulfate, 25 g potassium sodium tartrate, 0.05 g thiourea, 10 g formaldehyde, 6 g sodium hydroxide, 0.1 g ammonium chloride, 0.5 g sodium silicate, and water was added to 1000 ml.

[0038] 20 g of PVA resin, 5 g of PTFE resin, 1 g of graphene oxide / carbon nanocomposite fiber, 1 g of 3D-MXene@Cu and 20 g of casting components (8 g of anhydrous ethanol, 8 g of xylene, 2 g of polyvinyl butyrate, 1 g of oleic acid, 0.5 g of glycerol, and 0.5 g of dibutyl phthalate) were mixed and ball-milled on a planetary ball mill for 5 h to obtain a slurry. The slurry was vacuum-defoamed and then cast on a flat glass plate to form a film. The obtained film was kept in an oven at 180°C for 2 h and cooled to room temperature with the furnace to obtain an electromagnetic shielding layer 3 with a thickness of 0.15 mm. Example 2

[0039] An astronaut outbound cable, having a flat ribbon structure, comprising an X-ETFE outer sheath 1, and a mica wrapping tape layer 2 and an electromagnetic shielding layer 3 arranged inside the X-ETFE outer sheath 1, wherein the electromagnetic shielding layer 3 covers and fixes three cable cores, and each cable core is composed of an ETFE inner sheath 4 and a silver-plated copper stranded conductor 5;

[0040] The electromagnetic shielding layer 3 includes PVA resin, PTFE resin, graphene oxide / carbon nanocomposite fiber and 3D-MXene@Cu in a mass ratio of 20:5:1:1;

[0041] The preparation method of the electromagnetic shielding layer 3 is as follows:

[0042] Appropriate heating was performed to dissolve 8 g of polyacrylonitrile and 4 g of porogen PVP in 100 ml of DMF to obtain a composite solution, and then 0.1 g of graphene was added and ultrasonically oscillated for 30 min to prepare an electrospinning solution, and an appropriate amount of the electrospinning solution was injected into a syringe, and the distance between the needle and the receiver was 15 cm, the voltage was set to 20 kV, and the spinning speed was 0.5 ml / h. Electrospinning was performed, and the collected nanofibers were vacuum dried for 12 h to obtain a composite fiber precursor, and the composite fiber precursor was soaked in deionized water at 100 ° C for 2 h to wash and remove the porogen PVP to form a porous structure, and then placed in a muffle furnace and heated to 300 ° C at a rate of 1 ° C / min in an air atmosphere for pre-oxidation treatment for 5 h, and then heated to 900 ° C at a rate of 10 ° C / min under nitrogen protection for carbonization treatment for 2 h to obtain a graphene oxide / carbon nanocomposite fiber with a porous structure;

[0043] Take commercially available MXene (Ti3C2T x)5g was dispersed in 10wt% 500ml octadecyltrimethylammonium bromide solution, stirred and reacted for 24h in a water bath at 40℃, then filtered, the obtained solid was washed with deionized water and frozen with liquid nitrogen, and then placed in a freeze dryer, freeze-dried at -80℃ and 10 Pa for 48h to obtain 3D-MXene, 3D-MXene was added to 10g / L SnCl2 solution for sensitization treatment for 30min, and then added to 0.1 g / L PdCl2 solution for activation treatment for 30min, and finally the product was washed with deionized water until neutral and added to 40℃ chemical plating solution for copper plating for 2min to obtain 3D-MXene@Cu, the composition of the chemical plating solution is as follows: 10g copper sulfate, 25g potassium sodium tartrate, 0.05g thiourea, 10g formaldehyde, 6g sodium hydroxide, 0.1g ammonium chloride, 0.5g sodium silicate, and water was added to 1000ml;

[0044] 20 g of PVA resin, 5 g of PTFE resin, 1 g of graphene oxide / carbon nanocomposite fiber, 1 g of 3D-MXene@Cu and 20 g of casting components (8 g of anhydrous ethanol, 8 g of xylene, 2 g of polyvinyl butyrate, 1 g of oleic acid, 0.5 g of glycerol, and 0.5 g of dibutyl phthalate) were mixed and ball-milled on a planetary ball mill for 5 h to obtain a slurry. The slurry was vacuum-defoamed and then cast on a flat glass plate to form a film. The obtained film was kept in an oven at 180°C for 2 h and cooled to room temperature with the furnace to obtain an electromagnetic shielding layer 3 with a thickness of 0.15 mm. Example 3

[0045] An astronaut outbound cable, having a flat ribbon structure, comprising an X-ETFE outer sheath 1, and a mica wrapping tape layer 2 and an electromagnetic shielding layer 3 arranged inside the X-ETFE outer sheath 1, wherein the electromagnetic shielding layer 3 covers and fixes three cable cores, and each cable core is composed of an ETFE inner sheath 4 and a silver-plated copper stranded conductor 5;

[0046] The electromagnetic shielding layer 3 includes PVA resin, PTFE resin, graphene oxide / carbon nanocomposite fiber and 3D-MXene@Cu in a mass ratio of 20:5:1:1;

[0047] The preparation method of the electromagnetic shielding layer 3 is as follows:

[0048] Appropriate heating was performed to dissolve 8 g of polyacrylonitrile and 4 g of porogen PVP in 100 ml of DMF to obtain a composite solution, and then 0.1 g of graphene was added and ultrasonically oscillated for 30 min to prepare an electrospinning solution, and an appropriate amount of the electrospinning solution was injected into a syringe, and the distance between the needle and the receiver was 15 cm, the voltage was set to 20 kV, and the spinning speed was 0.5 ml / h. Electrospinning was performed, and the collected nanofibers were vacuum dried for 12 h to obtain a composite fiber precursor, and the composite fiber precursor was soaked in deionized water at 100 ° C for 2 h to wash and remove the porogen PVP to form a porous structure, and then placed in a muffle furnace and heated to 400 ° C at a rate of 1 ° C / min in an air atmosphere for pre-oxidation treatment for 5 h, and then heated to 1000 ° C at a rate of 10 ° C / min under nitrogen protection for carbonization treatment for 2 h to obtain a graphene oxide / carbon nanocomposite fiber with a porous structure;

[0049] Take commercially available MXene (Ti3C2T x )5g was dispersed in 10wt% 500ml octadecyltrimethylammonium bromide solution, stirred and reacted for 24h in a water bath at 40℃, then filtered, the obtained solid was washed with deionized water and frozen with liquid nitrogen, and then placed in a freeze dryer, freeze-dried at -80℃ and 10 Pa for 48h to obtain 3D-MXene, 3D-MXene was added to 10g / L SnCl2 solution for sensitization treatment for 30min, and then added to 0.1 g / L PdCl2 solution for activation treatment for 30min, and finally the product was washed with deionized water until neutral and added to 40℃ chemical plating solution for copper plating for 2min to obtain 3D-MXene@Cu, the composition of the chemical plating solution is as follows: 10g copper sulfate, 25g potassium sodium tartrate, 0.05g thiourea, 10g formaldehyde, 6g sodium hydroxide, 0.1g ammonium chloride, 0.5g sodium silicate, and water was added to 1000ml;

[0050] 20 g of PVA resin, 5 g of PTFE resin, 1 g of graphene oxide / carbon nanocomposite fiber, 1 g of 3D-MXene@Cu and 20 g of casting components (8 g of anhydrous ethanol, 8 g of xylene, 2 g of polyvinyl butyrate, 1 g of oleic acid, 0.5 g of glycerol, and 0.5 g of dibutyl phthalate) were mixed and ball-milled on a planetary ball mill for 5 h to obtain a slurry. The slurry was vacuum-defoamed and then cast on a flat glass plate to form a film. The obtained film was kept in an oven at 180°C for 2 h and cooled to room temperature with the furnace to obtain an electromagnetic shielding layer 3 with a thickness of 0.15 mm.

[0051] Comparative Example 1:

[0052] The method is basically the same as Example 2, except that the porogen PVP is not added during the preparation of the graphene oxide / carbon nanocomposite fibers;

[0053] This comparative example provides an astronaut extravehicular cable, which has a flat ribbon structure and includes an X-ETFE outer sheath 1, a mica wrapping tape layer 2 and an electromagnetic shielding layer 3 arranged inside the X-ETFE outer sheath 1, and the electromagnetic shielding layer 3 covers and fixes three cable cores, and each cable core is composed of an ETFE inner sheath 4 and a silver-plated copper stranded conductor 5;

[0054] The electromagnetic shielding layer 3 includes PVA resin, PTFE resin, graphene oxide / carbon nanocomposite fiber and 3D-MXene@Cu in a mass ratio of 20:5:1:1;

[0055] The preparation method of the electromagnetic shielding layer 3 is as follows:

[0056] Appropriate heating was performed to dissolve 8 g of polyacrylonitrile in 100 ml of DMF to obtain a polyacrylonitrile solution, and then 0.1 g of graphene was added and ultrasonically oscillated for 30 min to prepare an electrospinning solution, and an appropriate amount of the electrospinning solution was injected into a syringe, and the distance between the needle and the receiver was 15 cm, the voltage was set to 20 kV, and the spinning speed was 0.5 ml / h. Electrospinning was performed, and the collected nanofibers were vacuum dried for 12 h to obtain a composite fiber precursor, and the composite fiber precursor was soaked in deionized water at 100 ° C for 2 h for washing, and then placed in a muffle furnace and heated to 300 ° C at a rate of 1 ° C / min in an air atmosphere for pre-oxidation treatment for 5 h, and then heated to 900 ° C at a rate of 10 ° C / min under nitrogen protection for carbonization treatment for 2 h to obtain graphene oxide / carbon nanocomposite fibers;

[0057] Take commercially available MXene (Ti3C2T x )5g was dispersed in 10wt% 500ml octadecyltrimethylammonium bromide solution, stirred and reacted for 24h in a water bath at 40℃, then filtered, the obtained solid was washed with deionized water and frozen with liquid nitrogen, and then placed in a freeze dryer, freeze-dried at -80℃ and 10 Pa for 48h to obtain 3D-MXene, 3D-MXene was added to 10g / L SnCl2 solution for sensitization treatment for 30min, and then added to 0.1 g / L PdCl2 solution for activation treatment for 30min, and finally the product was washed with deionized water until neutral and added to 40℃ chemical plating solution for copper plating for 2min to obtain 3D-MXene@Cu, the composition of the chemical plating solution is as follows: 10g copper sulfate, 25g potassium sodium tartrate, 0.05g thiourea, 10g formaldehyde, 6g sodium hydroxide, 0.1g ammonium chloride, 0.5g sodium silicate, and water was added to 1000ml;

[0058] 20 g of PVA resin, 5 g of PTFE resin, 1 g of graphene oxide / carbon nanocomposite fiber, 1 g of 3D-MXene@Cu and 20 g of casting components (8 g of anhydrous ethanol, 8 g of xylene, 2 g of polyvinyl butyrate, 1 g of oleic acid, 0.5 g of glycerol, and 0.5 g of dibutyl phthalate) were mixed and ball-milled on a planetary ball mill for 5 h to obtain a slurry. The slurry was vacuum-defoamed and then cast on a flat glass plate to form a film. The obtained film was kept in an oven at 180°C for 2 h and cooled to room temperature with the furnace to obtain an electromagnetic shielding layer 3 with a thickness of 0.15 mm.

[0059] Comparative Example 2:

[0060] The same as Example 2, except that commercially available MXene (Ti3C2T x ) Replace 3D-MXene for chemical copper plating;

[0061] This comparative example provides an astronaut extravehicular cable, which has a flat ribbon structure and includes an X-ETFE outer sheath 1, a mica wrapping tape layer 2 and an electromagnetic shielding layer 3 arranged inside the X-ETFE outer sheath 1, and the electromagnetic shielding layer 3 covers and fixes three cable cores, and each cable core is composed of an ETFE inner sheath 4 and a silver-plated copper stranded conductor 5;

[0062] The electromagnetic shielding layer 3 includes PVA resin, PTFE resin, graphene oxide / carbon nanocomposite fiber and MXene@Cu in a mass ratio of 20:5:1:1;

[0063] The preparation method of the electromagnetic shielding layer 3 is as follows:

[0064] Appropriate heating was performed to dissolve 8 g of polyacrylonitrile and 4 g of porogen PVP in 100 ml of DMF to obtain a composite solution, and then 0.1 g of graphene was added and ultrasonically oscillated for 30 min to prepare an electrospinning solution, and an appropriate amount of the electrospinning solution was injected into a syringe, and the distance between the needle and the receiver was 15 cm, the voltage was set to 20 kV, and the spinning speed was 0.5 ml / h. Electrospinning was performed, and the collected nanofibers were vacuum dried for 12 h to obtain a composite fiber precursor, and the composite fiber precursor was soaked in deionized water at 100 ° C for 2 h to wash and remove the porogen PVP to form a porous structure, and then placed in a muffle furnace and heated to 300 ° C at a rate of 1 ° C / min in an air atmosphere for pre-oxidation treatment for 5 h, and then heated to 900 ° C at a rate of 10 ° C / min under nitrogen protection for carbonization treatment for 2 h to obtain a graphene oxide / carbon nanocomposite fiber with a porous structure;

[0065] Take commercially available MXene (Ti3C2T x)5g was added to 10g / L SnCl2 solution for sensitization treatment for 30min, then added to 0.1g / L PdCl2 solution for activation treatment for 30min, and finally the product was washed with deionized water until neutral and added to 40℃ chemical plating solution for copper plating for 2min to obtain MXene@Cu. The composition of the chemical plating solution is as follows: 10g copper sulfate, 25g potassium sodium tartrate, 0.05g thiourea, 10g formaldehyde, 6g sodium hydroxide, 0.1g ammonium chloride, 0.5g sodium silicate, and water was added to 1000ml;

[0066] 20 g of PVA resin, 5 g of PTFE resin, 1 g of graphene oxide / carbon nanocomposite fiber, 1 g of MXene@Cu and 20 g of casting components (8 g of anhydrous ethanol, 8 g of xylene, 2 g of polyvinyl butyrate, 1 g of oleic acid, 0.5 g of glycerol, and 0.5 g of dibutyl phthalate) were mixed and ball-milled on a planetary ball mill for 5 h to obtain a slurry. The slurry was vacuum-defoamed and then cast on a flat glass plate to form a film. The obtained film was kept in an oven at 180°C for 2 h and cooled to room temperature with the furnace to obtain an electromagnetic shielding layer 3 with a thickness of 0.15 mm.

[0067] Comparative Example 3:

[0068] The same as Example 2, except that commercially available MXene (Ti3C2T x ) instead of 3D-MXene@Cu;

[0069] This comparative example provides an astronaut extravehicular cable, which has a flat ribbon structure and includes an X-ETFE outer sheath 1, a mica wrapping tape layer 2 and an electromagnetic shielding layer 3 arranged inside the X-ETFE outer sheath 1, and the electromagnetic shielding layer 3 covers and fixes three cable cores, and each cable core is composed of an ETFE inner sheath 4 and a silver-plated copper stranded conductor 5;

[0070] The electromagnetic shielding layer 3 includes PVA resin, PTFE resin, graphene oxide / carbon nanocomposite fiber and MXene in a mass ratio of 20:5:1:1;

[0071] The preparation method of the electromagnetic shielding layer 3 is as follows:

[0072] Appropriate heating was performed to dissolve 8 g of polyacrylonitrile and 4 g of porogen PVP in 100 ml of DMF to obtain a composite solution, and then 0.1 g of graphene was added and ultrasonically oscillated for 30 min to prepare an electrospinning solution, and an appropriate amount of the electrospinning solution was injected into a syringe, and the distance between the needle and the receiver was 15 cm, the voltage was set to 20 kV, and the spinning speed was 0.5 ml / h. Electrospinning was performed, and the collected nanofibers were vacuum dried for 12 h to obtain a composite fiber precursor, and the composite fiber precursor was soaked in deionized water at 100 ° C for 2 h to wash and remove the porogen PVP to form a porous structure, and then placed in a muffle furnace and heated to 300 ° C at a rate of 1 ° C / min in an air atmosphere for pre-oxidation treatment for 5 h, and then heated to 900 ° C at a rate of 10 ° C / min under nitrogen protection for carbonization treatment for 2 h to obtain a graphene oxide / carbon nanocomposite fiber with a porous structure;

[0073] 20 g of PVA resin, 5 g of PTFE resin, 1 g of graphene oxide / carbon nanocomposite fiber, and 1 g of commercially available MXene (Ti3C2T x ) and 20g of casting components (8g of anhydrous ethanol, 8g of xylene, 2g of polyvinyl butyrate, 1g of oleic acid, 0.5g of glycerol, and 0.5g of dibutyl phthalate), and ball-milled on a planetary ball mill for 5 hours to obtain a slurry. The slurry is vacuum-defoamed and then cast on a flat glass plate to form a film. The obtained film is kept warm in an oven at 180°C for 2 hours, and cooled to room temperature with the furnace to obtain an electromagnetic shielding layer 3 with a thickness of 0.15 mm.

[0074] Comparative Example 4:

[0075] The same as Example 2, except that 3D-MXene@Cu is replaced by 3D-MXene;

[0076] This comparative example provides an astronaut extravehicular cable, which has a flat ribbon structure and includes an X-ETFE outer sheath 1, a mica wrapping tape layer 2 and an electromagnetic shielding layer 3 arranged inside the X-ETFE outer sheath 1, and the electromagnetic shielding layer 3 covers and fixes three cable cores, and each cable core is composed of an ETFE inner sheath 4 and a silver-plated copper stranded conductor 5;

[0077] The electromagnetic shielding layer 3 includes PVA resin, PTFE resin, graphene oxide / carbon nanocomposite fiber and 3D-MXene@Cu in a mass ratio of 20:5:1:1;

[0078] The preparation method of the electromagnetic shielding layer 3 is as follows:

[0079] Appropriate heating was performed to dissolve 8 g of polyacrylonitrile and 4 g of porogen PVP in 100 ml of DMF to obtain a composite solution, and then 0.1 g of graphene was added and ultrasonically oscillated for 30 min to prepare an electrospinning solution, and an appropriate amount of the electrospinning solution was injected into a syringe, and the distance between the needle and the receiver was 15 cm, the voltage was set to 20 kV, and the spinning speed was 0.5 ml / h. Electrospinning was performed, and the collected nanofibers were vacuum dried for 12 h to obtain a composite fiber precursor, and the composite fiber precursor was soaked in deionized water at 100 ° C for 2 h to wash and remove the porogen PVP to form a porous structure, and then placed in a muffle furnace and heated to 300 ° C at a rate of 1 ° C / min in an air atmosphere for pre-oxidation treatment for 5 h, and then heated to 900 ° C at a rate of 10 ° C / min under nitrogen protection for carbonization treatment for 2 h to obtain a graphene oxide / carbon nanocomposite fiber with a porous structure;

[0080] Take commercially available MXene (Ti3C2T x )5g was dispersed in 10wt% 500ml octadecyltrimethylammonium bromide solution, stirred in a water bath at 40℃ for 24h and filtered, the obtained solid was washed with deionized water and frozen with liquid nitrogen, and then placed in a freeze dryer and freeze-dried at -80℃ and 10 Pa for 48h to obtain 3D-MXene;

[0081] 20 g of PVA resin, 5 g of PTFE resin, 1 g of graphene oxide / carbon nanocomposite fiber, 1 g of 3D-MXene and 20 g of casting components (8 g of anhydrous ethanol, 8 g of xylene, 2 g of polyvinyl butyrate, 1 g of oleic acid, 0.5 g of glycerol, and 0.5 g of dibutyl phthalate) were mixed, and the mixture was ball-milled on a planetary ball mill for 5 h to obtain a slurry. The slurry was vacuum-defoamed and then cast on a flat glass plate to form a film. The obtained film was kept in an oven at 180° C. for 2 h, and then cooled to room temperature with the furnace to obtain an electromagnetic shielding layer 3 with a thickness of 0.15 mm.

[0082] Performance testing:

[0083] The electromagnetic shielding layers prepared in Examples 1-3 and Comparative Examples 1-4 were made into test samples;

[0084] Tensile strength test: using the test method of GB / T 7753-1987, the tensile speed of the sample is 300mm / min;

[0085] Electromagnetic Interference Shielding Test: According to ASTM ES7-83 and ASTM D4935-18, EMI shielding measurements were performed on the specimens using a coaxial test cell (APC-7 connector) and an Agilent N5247A carrier network analyzer, with a test frequency range of 8.2-12.4 GHz.

[0086] The test results are shown in Table 1 below:

[0087]

[0088] It can be seen from Table 1 above that the electromagnetic shielding layer prepared by the present invention has good mechanical properties and excellent electromagnetic shielding effectiveness.

[0089] From the comparison of Examples 1-3, it can be seen that the pre-oxidation treatment temperature and the carbonization treatment temperature will affect the mechanics and electromagnetic shielding effectiveness of the electromagnetic shielding layer.

[0090] From the comparison between Example 2 and Comparative Example 1, it can be seen that the porous structure electromagnetic shielding layer on the graphene oxide / carbon nanocomposite fiber plays a positive role in improving the mechanical properties and electromagnetic shielding effectiveness.

[0091] By comparing Example 2 with Comparative Example 2, it can be seen that the 3D-MXene with a three-dimensional structure has a more obvious improvement on the mechanical properties and electromagnetic shielding effectiveness of the electromagnetic shielding layer after copper plating.

[0092] By comparing Example 2 with Comparative Examples 3 and 4, it can be seen that the copper plating layer on the surface of 3D-MXene plays a positive role in improving the mechanics of the electromagnetic shielding layer and the electromagnetic shielding effectiveness.

[0093] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An astronaut out-of-vehicle cable, characterized in that: It comprises an outer sheath, and a mica wrapping tape layer and an electromagnetic shielding layer arranged inside the outer sheath, wherein the electromagnetic shielding layer covers and fixes a plurality of cable cores, and the cable cores are composed of a conductor and an inner sheath; The electromagnetic shielding layer comprises a matrix resin, graphene oxide / carbon nanocomposite fibers and 3D-MXene@M, wherein M is a transition metal element; The preparation method of the electromagnetic shielding layer is as follows: Polyacrylonitrile and a porogen are dissolved in an organic solvent, and graphene is added to prepare an electrospinning solution, a composite fiber precursor is prepared by an electrospinning machine, the composite fiber precursor is dried and the porogen is removed to form a porous structure, a pre-oxidation treatment is performed in an air atmosphere, and then a carbonization treatment is performed under nitrogen protection to obtain a graphene oxide / carbon nanocomposite fiber with a porous structure; Disperse MXene in a quaternary ammonium salt solution at 40-60°C and stir for 12-36 hours before filtering. The resulting solid is frozen with liquid nitrogen and then freeze-dried in a freeze dryer to obtain 3D-MXene. Form an M layer on its surface by chemical plating to obtain 3D-MXene@M. The matrix resin, 3D-MXene@M and graphene oxide / carbon nanocomposite fibers are prepared into a slurry, and then a film is formed by a casting method.

2. The astronaut extravehicular cable according to claim 1, characterized in that: The porogen is any one or more combinations of polyethylene glycol, hydroxypropyl cellulose, povidone, urea, and polyvinyl pyrrolidone.

3. The astronaut extravehicular cable according to claim 1, characterized in that: The pre-oxidation temperature is 200-400°C, and the carbonization temperature is 800-1000°C.

4. The astronaut extravehicular cable according to claim 1, characterized in that: The quaternary ammonium salt is alkyl trimethyl ammonium bromide, wherein the number of carbon atoms of the alkyl group is ≥10.

5. The astronaut extravehicular cable according to claim 1, characterized in that: 3D-MXene aerogel needs to be sensitized and activated before chemical plating.

6. The astronaut extravehicular cable according to claim 1, characterized in that: The organic solvent is a dipolar solvent.

7. The astronaut extravehicular cable according to claim 1, characterized in that: The mass ratio of matrix resin, graphene oxide / carbon nanocomposite fiber and 3D-MXene@M is 10-50:1-5:1-5.

8. The astronaut extravehicular cable according to claim 1, characterized in that: The matrix resin is any one or more combinations of polyvinyl alcohol resin, epoxy resin, polyester resin, bismaleimide resin, thermosetting polyimide resin, furan resin, polybutadiene resin, silicone resin, polytetrafluoroethylene resin, and polyvinylidene fluoride resin.

9. The astronaut extravehicular cable according to claim 1, characterized in that: M is any one of Ni, Ag, and Cu.

Citation Information

Patent Citations

  • Graphene / carbon nanometer porous fiber and its preparation method and use

    CN106480552A

  • MXene aerogel / epoxy resin electromagnetic-shielding nano composite and preparation method thereof

    CN109897343A